Kepastian Hukum Perolehan Hak Atas Kekayaan Intelektual - Maria Alfons (Jatiswara, 2016)
Indonesia is one country that has a lot of islands, culture and even the crops or products produced or the results of intellectual work which later developed into an attractive arena in the world, especially in the fields of economy, industry and international trade. Acquisition of legal certainty is a matter that can only be answered normatively based on the legislation in force, not sociological, but legal certainty normatively is when a rule is made and legislated for sure will set out clear and logical, in the sense not cause doubts -raguan (multi-interpretation) and logical in the sense of a system of norms with other norms so as not to clash or conflict norms arising from uncertainty. The existence of a certificate of physical evidence data and data juridical evidence, the certificate is a guarantee of the acquisition of legal certainty to protect intellectual property, Obtaining legal certainty in the field of intellectual property is in order to protect natural resources and biodiversity are the products of society.